Coexpression Analysis Identifies Two Oxidoreductases Involved in the Biosynthesis of the Monoterpene Acid Moiety of Natural Pyrethrin Insecticides in Tanacetum cinerariifolium. Issue 1 (9th November 2017) - Xu, Haiyang; Moghe, Gaurav D.; Wiegert-Rininger, Krystle; Schilmiller, Anthony L.; Barry, Cornelius S.; Last, Robert L.; Pichersky, Eran
Abstract : A set of dehydrogenases are involved in the synthesis of trans-chrysanthemic acid, the terpene moiety of the natural insecticide pyrethrins. Abstract: Flowers of Tanacetum cinerariifolium produce a set of compounds known collectively as pyrethrins, which are commercially important pesticides that are strongly toxic to flying insects but not to most vertebrates. A pyrethrin molecule is an ester consisting of either trans-chrysanthemic acid or its modified form, pyrethric acid, and one of three alcohols, jasmolone, pyrethrolone, and cinerolone, that appear to be derived from jasmonic acid. Chrysanthemyl diphosphate synthase (CDS), the first enzyme involved in the synthesis of trans-chrysanthemic acid, was characterized previously and its gene isolated. TcCDS produces free trans-chrysanthemol in addition to trans-chrysanthemyl diphosphate, but the enzymes responsible for the conversion of trans-chrysanthemol to the corresponding aldehyde and then to the acid have not been reported. We used an RNA sequencing-based approach and coexpression correlation analysis to identify several candidate genes encoding putative trans-chrysanthemol and trans-chrysanthemal dehydrogenases. We functionally characterized the proteins encoded by these genes using a combination of in vitro biochemical assays and heterologous expression in planta to demonstrate that TcADH2 encodes an enzyme that oxidizes trans-chrysanthemol to trans-chrysanthemal, while TcALDH1 encodes an enzyme that oxidizes trans-chrysanthemal into trans-chrysanthemic acid. Transient coexpression of TcADH2 and TcALDH1 together with TcCDS in Nicotiana benthamiana leaves results in the production of trans-chrysanthemic acid as well as several other side products. The majority (58%) of trans-chrysanthemic acid was glycosylated or otherwise modified. Overall, these data identify key steps in the biosynthesis of pyrethrins and demonstrate the feasibility of metabolic engineering to produce components of these defense compounds in a heterologous host.